Perilaku Merokok Berubungan dengan Aliran Puncak Ekspirasi Pria Dewasa - Srimiyati, Srimiyati; Ajul, Keristina; Surani, Vincencius (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between smoking behavior and peak expiratory flow in adult men. The method used is a descriptive correlation with a cross-sectional approach. The total research sample was 67 respondents taken using the purposive sampling technique. The instrument used was a questionnaire to measure age and smoking behavior, while peak expiratory flow was measured using a peak flow meter. Data analysis used the Kendall tau_b test. The research results show that the p-value is 0.003 and τ = -.347. In conclusion, there is a significant relationship between smoking behavior and peak expiratory flow in adult men with a weak correlation level and tends to have a negative direction. Keywords: Peak Expiratory Flow, Smoking Behavior, Breathing, Adult Men, Cigarettes